Kahoot Gamification: Fostering Critical Thinking in Arabic Listening Comprehension - Sholihatul Atik Hikmawati; Al Lastu Nurul Fatim; M. Abdul Hamid; A. Samsul Ma’arif; Bakri Muhammad Bakhiet (Alsina : Journal of Arabic Studies, 2025)
In the era of digital transformation, education increasingly demands innovative pedagogical approaches that not only enhance language proficiency but also cultivate students’ critical thinking skills. This study explores how Kahoot gamification supports the development of critical thinking in Arabic listening comprehension. The research employed a qualitative approach with a single instrumental case study design to examine the integration of Kahoot-based learning activities and their cognitive outcomes. Data were collected through participant observation, documentation, and interviews involving 39 undergraduate students from the Faculty of Sharia, UIN Maulana Malik Ibrahim Malang, class of 2024. The data were analyzed using the interactive model of Miles and Huberman to identify indicators of critical thinking based on Facione’s six dimensions: interpretation, analysis, evaluation, inference, explanation, and self-regulation. The findings revealed that Kahoot gamification was implemented through four learning activities: song playback, simple dialogue, short film, and short story. Each activity stimulated distinct aspects of critical thinking, with song and short film activities generating the most active responses. The study suggests that Kahoot gamification may serve as an effective pedagogical tool to foster engagement and higher-order thinking in Arabic listening instruction, particularly for beginner-level learners.